Comparative Study Of Partus Set Decontamination: Chlorine And Enzymatic Alkazyme In Infection Prevention - Ambar Susanti; Listyaning Eko Martanti; Dhita Aulia Octaviani (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
Introduction: Childbirth is a daily miracle and a source of joy for families. To reduce maternal and neonatal mortality rates, providing clean and safe delivery care is essential, including infection prevention. One method of infection prevention is decontaminating the partus set. Chlorine-based decontamination is commonly used but has drawbacks such as causing corrosion at low pH levels. Enzymatic solutions like Alkazyme offer an alternative for decontaminating delivery equipment. Objectives: This study aims to describe the decontamination of the partus set using chlorine and enzymatic Alkazyme as an infection prevention effort at Boja II Community Health Center. Methods: This was a descriptive observational study. The samples consisted of delivery instruments used in childbirth, selected through accidental sampling. The study focused on a single variable: the decontamination of partus sets using chlorine and enzymatic Alkazyme. Results: Decontamination using chlorine at Boja II Health Center showed bacterial presence of 315 CFU/cm² with an average of 52.5 CFU/cm². Meanwhile, decontamination using enzymatic Alkazyme resulted in 127.4 CFU/cm² with an average of 3.2 CFU/cm². Conclusions: Enzymatic Alkazyme leaves fewer bacterial residues than chlorine. Midwives can consider using enzymatic solutions as an alternative method for decontaminating partus sets.